Immunological Status of the Reproductive Tract of Ewes During Follicular and Luteal Phases - Al-Medhtiy, Morteta H. (2009)

(untitled)
The levels of uterine Secretory-IgA (S-IgA) and numbers of plasma cells were measured to observe the differences between two stages of estrous cycle (follicular and luteal phases) in the healthy cycling non pregnant ewes. Twelve local crossbreed (Malin) ewes were used in this study and they were divided into two groups of 6 animals each according to the stages of estrous cycle. All ewes were subjected to estrous synchronization and were allowed to undergo one natural estrous cycle after the removal of the sponge. All animals were slaughtered at the end of the experiment. The uterine mucus was harvested by flushing with a mixture of protease inhibitor cocktail in distilled water. For both stages, the level of uterine S-IgA was quantified by using ELISA and Methyl Green Pyronine staining was used to quantify the plasma cell in the mucosa of the uterine horn and oviduct of ewe’s reproductive tract. H&E stain was used to evaluate the histological changes of endometrium during follicular and luteal phases of ewe. The protocol of the study was approved by the Faculty’s animal care and use committee (animal utilization protocol number: 08R26/Jun 08-May 09). The S-IgA level and the number of plasma cells in the reproductive tract of ewe were significantly higher (P<0.01) in the follicular phase as compared to those values in the luteal phase.